The mystery in Venice - Stilton, Geronimo; De Pretto, Lorenzo 1966-; Corsi, Davide; Heim, Julia; Petronio, Kay (New York Scholastic, Inc., 2012)
Accepting an ugly crystal figurine from Petunia Pretty Paws, Geronimo Stilton discovers a mysterious message inside the figurine from a Venetian mouse who requires assistance.
Based on original idea by Isabetta Dami.
Original title: Il mistero della gondola di cristallo.
"English translation © 2012 by Atlantyca S.p.A."
Geronimo Stilton is a book character who is the attributed author.
RL3.
007-010.
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Juvenile fiction; Journalists -- Juvenile fiction; Mice -- Fiction; Mystery and detective stories; Mice -- Fiction; Venice (Italy) -- Juvenile fiction; Venice (Italy) -- Fiction; Venice (Italy) -- Fiction; Adventure fiction; Humorous fiction; Mystery fiction